Monitoring and Analysis of Expansion Relief Grooves to Control the Arch Expansion Disease - Xiangyu Li; Xuesong Mao; Qian Wu; Pei He (Buildings, 2025)
Expansion relief groove (ERG) controlling excess arch expansion has become a research hotspot. Based on statistical arch expansion data, this paper proposes a novel structural design for ERG, selecting asphalt-treated base (ATB-25) and graded gravel (GG) as fill materials for trial paving. Through three years of monitoring, the temperature, stress, and displacement across the two solutions were comparatively analyzed to evaluate their control effectiveness. The results indicated five points. (1) The reasonable spacing of the expansion through should be 200 m, and the width should not be less than 50 cm in ERG structure design. (2) The annual temperature difference of ATB-25 ERG (55 °C) > GG ERG (51 °C) > cement-treated base (CTB) (47 °C). The large annual temperature difference causes the expansion of the base. (3) The performance of ERGs is highly correlated with the seasonal alternation. The compressive stress increases in summer, resulting in compressive deformation, and decreases in winter, resulting in extended deformation. (4) According to three years of monitoring, the plastic deformation accumulated, and the compression deformation in the two ERGs increased to 155% and 943.47% of that in the first year. The expansion pressure in the base layer is constrained, resulting in compression deformation of the base. (5) GG is more suitable as the filler of the ERG to deal with arch expansion disease and demonstrates excellent cost-effectiveness.